2004
DOI: 10.1002/chin.200431006
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Evidence for Protonated Water Clusters Forming Nanoscale Cages.

Abstract: n = 4-27) are characterized by IR spectroscopy of OH stretches in the gas phase. Spectral changes with cluster size demonstrate that the chain structures at small sizes (n < 10) develop into two-dimensional net structures (10 < n < 21), and then into nanometer-scaled cages (n > 21). -(MIYAZAKI, M.; FUJII*, A.; EBATA, T.; MIKAMI, N.; Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
143
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 1 publication
11
143
0
Order By: Relevance
“…39͒ and a production run, sampling the micro-canonical ensemble, of 100 ps for the small clusters ͓H + ͑H 2 O͒ n ͑n = 2 -10͔͒ and 50 ps for the "magic" protonated H + ͑H 2 O͒ 21 cluster. In the experimental studies, 31,[34][35][36] the exact temperatures of the water clusters are either unknown or uncertain. It is estimated that the temperature is in the range of 170± 20 K for the magic protonated water clusters.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…39͒ and a production run, sampling the micro-canonical ensemble, of 100 ps for the small clusters ͓H + ͑H 2 O͒ n ͑n = 2 -10͔͒ and 50 ps for the "magic" protonated H + ͑H 2 O͒ 21 cluster. In the experimental studies, 31,[34][35][36] the exact temperatures of the water clusters are either unknown or uncertain. It is estimated that the temperature is in the range of 170± 20 K for the magic protonated water clusters.…”
Section: Methodsmentioning
confidence: 99%
“…It is estimated that the temperature is in the range of 170± 20 K for the magic protonated water clusters. 30,34,[40][41][42] Thus in the current work, we have simulated the cluster H + ͑H 2 O͒ 21 at 100, 125, 150, 175, and 200 K for comparison. To properly sample the high frequency vibrational modes in the system, the time step of integration is set to 0.5 fs, although a shorter time step of 0.2 fs is also tested ͓see EPAPS ͑Ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, the IR spectra are being used to identify the geometrical structure of small clusters. [10,11,13,22,23] At the same time, theoretical IR spectra of water clusters are frequently simulated based on quantum-chemical computations to help determine the molecular structure of water clusters through comparing with experimental results. [5,6,[24][25][26] Regarding quantum-chemical studies of vibrations of larger clusters, the IR spectra of different (H 2 O) 20 isomers were calculated by Fanourgakis et al at the level of MP2 theory, where they demonstrated the different spectral features for the isomers and that these features could be related to the spectra of their constituent fragments.…”
Section: Introductionmentioning
confidence: 99%
“…The information on the amount of water available for the hydrolysis of silanes and subsequent condensation has been studied by several spectroscopic techniques, such as FTIR [27][28][29] , Raman [30][31] , UV-vis, NMR 32 , neutron scattering, etc. [33][34] .…”
Section: Introductionmentioning
confidence: 99%